2019
DOI: 10.1371/journal.pone.0215752
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hepatic fibrosis and inflammation: Correlation between histopathological changes and Gd-EOB-DTPA-enhanced MR imaging

Abstract: Objective To evaluate the influence of an active inflammatory process in the liver on Gd-EOB-DTPA-enhanced MR imaging in patients with different degrees of fibrosis/cirrhosis. Material and methods Overall, a number of 91 patients (61 men and 30 women; mean age 58 years) were included in this retrospective study. The inclusion criteria for this study were Gd-EOB-DTPA-enhanced MRI of the liver and histopathological evaluation of fibrotic and inflammatory changes. T1-weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Thus, enhanced MRI is more reliable for staging hepatic fibrosis than diffusion-weighted MRI, besides hematologic and clinical parameters. Furthermore, previous studies demonstrated the potential of liver-specific Gd-EOB-DTPA-enhanced MRI in hepatic fibrosis assessment, in which the HBP after 20 min highly correlated with the degree of liver fibrosis [ 22 , 23 , 24 , 25 , 26 , 27 ]. In this study, we performed a systematic work on radiomics analysis based on Gd-EOB-DTPA-enhanced MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, enhanced MRI is more reliable for staging hepatic fibrosis than diffusion-weighted MRI, besides hematologic and clinical parameters. Furthermore, previous studies demonstrated the potential of liver-specific Gd-EOB-DTPA-enhanced MRI in hepatic fibrosis assessment, in which the HBP after 20 min highly correlated with the degree of liver fibrosis [ 22 , 23 , 24 , 25 , 26 , 27 ]. In this study, we performed a systematic work on radiomics analysis based on Gd-EOB-DTPA-enhanced MRI.…”
Section: Discussionmentioning
confidence: 99%
“…NLE was calculated as the relative enhancement on the pre-contrast images using the following formula: NLE = (SI HBP − SI DYN1 )/(SI DYN1 ), where SI DYN1 and SI HBP are the mean signal intensities of the segmented liver ROI in the mask phase and HBP, respectively. NLE is actually a time-domain feature reported to be associated with the liver fibrosis grade in existing studies [ 22 , 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Search for prognostic, diagnostic and therapeutic agents (Duval et al, 2015) continues, but always concerns the liver tissue itself, requiring the biopsy, which carries the risk of complications, such as infection and bleeding (Germani et al, 2011). Recently, scientists have agreed on the idea that non-invasive methods could be sufficiently informative (Verloh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Second, it also reflects the total number of hepatocytes. For instance, the decreased relative liver enhancement (RLE) in fibrosis and cirrhosis results from the fibrotic replacement of some normal hepatocytes of the liver parenchyma [ 19 ]. In particular, gadoxetic acid enhancement in the hepatobiliary phase (HBP) reflects the net difference between uptake and excretory transporter activity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%